Chronic kidney disease and bleeding risk in patients at high cardiovascular risk: a cohort study. (20th December 2017) - Ocak, G.; Rookmaaker, M. B.; Algra, A.; de Borst, G. J.; Doevendans, P. A.; Kappelle, L. J.; Verhaar, M. C.; Visseren, F. L.; ,
Abstract : Essentials The association between chronic kidney disease and bleeding is unknown. We followed 10 347 subjects at high cardiovascular risk for bleeding events. Chronic kidney disease was associated with a 1.5‐fold increased bleeding risk. Especially albuminuria rather than decreased kidney function was associated with bleeding events. Summary: Background: There are indications that patients with chronic kidney disease have an increased bleeding risk. Objectives: To investigate the association between chronic kidney disease and bleeding in patients at high cardiovascular risk. Methods: We included 10 347 subjects referred to the University Medical Center Utrecht (the Netherlands) from September 1996 to February 2015 for an outpatient visit with classic risk factors for arterial disease or with symptomatic arterial disease (Second Manifestation of Arterial disease [SMART] cohort). Patients were staged according to the KDIGO guidelines, on the basis of estimated glomerular filtration rate (eGFR) and albuminuria, and were followed for the occurrence of major hemorrhagic events until March 2015. Hazard ratios (HRs) with 95% confidence intervals (CIs) for bleeding were calculated with Cox proportional hazards analyses. Results: The incidence rate for bleeding in subjects with chronic kidney disease was 8.0 per 1000 person‐years and that for subjects without chronic kidney disease was 3.5 per 1000 person‐years. Patients with chronic kidney disease ( n  = 2443) had a 1.5‐fold (95% CI 1.2–1.9) increased risk of bleeding as compared with subjects without chronic kidney disease ( n  = 7904) after adjustment. Subjects with an eGFR of < 45 mL min −1  1.73 m –2 with albuminuria had a 3.5‐fold (95% CI 2.3–5.3) increased bleeding risk, whereas an eGFR of < 45 mL min −1  1.73 m –2 without albuminuria was not associated with an increased bleeding risk (HR 1.3, 95% CI 0.7–2.5). Conclusion: Chronic kidney disease is a risk factor for bleeding in patients with classic risk factors for arterial disease or with symptomatic arterial disease, especially in the presence of albuminuria.